The first use of purpose-built in artificial Chimney Swift habitat in Manitoba - Firlotte, Nicole; Poole, Timothy F.; Artuso, Christian; Breiter, C-Jae C.; Burns, Laura D.; Petersen, Stephen D.; Stewart, Barbara E.; Stewart, Robert E.A. (Blue Jay, 2020)
Previous attempts to provide purpose-built artificial chimneys in Manitoba for the threatened Chimney Swift (Chaetura pelagica) have not attracted swifts. A new design of artificial chimney was constructed in Winnipeg and moved to the Assiniboine Park Zoo. Chimney Swifts bred in this tower during the summer of 2019, the first confirmed use of purpose-built artifical habitat in western Canada.